WAKAF PRODUKTIF (CASH WAQF) DALAM PERSPEKTIF HUKUM ISLAM DAN MAQĀṢID AL-SHARĪ‘AH - Suryani Suryani; Yunal Isra (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
Cash waqf is a breakthrough in appropriate with religious principles (maqāṣid al-sharī’ah) and social demands of humanity. This program can synergize with government programs in order to realize the welfare of the people of Indonesia as a manifestation of the ideals of the Republic of Indonesia, as stated in the preamble of the 1945 Constitution. Judging from the principle of religious, cash waqf has also been exemplified by several companions of Rasullullah and the scholars from time to time. Call it like what has been exemplified by the Caliph ‘Umar ibn al-Khaṭṭāb when making a land in Khaibar as productive land that used as much as possible for the benefit of Muslims. In addition, this program has also had supported by law. MUI Fatwa Commission also stipulates that the cash waqf is a movement in accordance with the principles of the religion that brought prosperity to the human in here and hereafter. This paper is literature research with reference to several primary and secondary sources such as books or books relevant to the study.